Effect of thoracic and cervical joint mobilization on pulmonary function in stroke patients - Jang, Sang-Hun (J Phys Ther Sci, 2016)
[Purpose] This study aimed to conduct thoracic and cervical mobilization in stroke patients and determine its effects on respiratory function. [Subjects and Methods] Twenty-one stroke patients were studied. Subjects were divided into a control group (control group, n=11) who did not undergo thoracic and cervical joint mobilization, and an experimental group (thoracic and cervical mobilization group, n=10) who underwent thoracic and cervical joint mobilization. Forced vital capacity and forced expiratory volume in the first second, well-known indicators of respiratory capabilities, were measured. Peak cough flow was measured as an indicator of cough capability. [Results] After the exercise, respiratory function in the thoracic and cervical mobilization group showed statistically significant improvements demonstrated by increases in forced vital capacity, forced expiratory volume in the first second, and peak cough flow. [Conclusion] The findings indicate that thoracic and cervical mobilization can improve the thoracic movements of stroke patients resulting in improved pulmonary function.